1986
DOI: 10.1068/p150173
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Perspective Structure While Walking without Vision

Abstract: Experiments are reported of the nonvisual sensitivity of observers to their paths of locomotion and to the resulting changes in the structure of their perspectives, ie changes in the network of directions and distances spatially relating them to objects fixed in the surrounding environment. In the first experiment it was found that adults can keep up to date on the changing structure of their perspectives even in the absence of sights and sounds that specify changes in self-to-object relations. They do this ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
221
4
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(240 citation statements)
references
References 24 publications
13
221
4
2
Order By: Relevance
“…The role of egocentric reference systems in spatial memory is, at this point, well documented (e.g., Diwadkar & McNamara, 1997;Presson & Montello, 1994;Rieser, 1989;Rieser, Guth, & Hill, 1986; Roskos-Ewoldsen, McNamara, Shelton, & Carr, 1998;Shelton & McNamara, 1997a, 1997b; Sholl & Nolin, 1997). For example, Roskos-Ewoldsen et al (1998) had participants learn four-point paths (see Fig.…”
Section: Egocentric Reference Systemsmentioning
confidence: 96%
“…The role of egocentric reference systems in spatial memory is, at this point, well documented (e.g., Diwadkar & McNamara, 1997;Presson & Montello, 1994;Rieser, 1989;Rieser, Guth, & Hill, 1986; Roskos-Ewoldsen, McNamara, Shelton, & Carr, 1998;Shelton & McNamara, 1997a, 1997b; Sholl & Nolin, 1997). For example, Roskos-Ewoldsen et al (1998) had participants learn four-point paths (see Fig.…”
Section: Egocentric Reference Systemsmentioning
confidence: 96%
“…Given that these STP cells distinguish self-produced from external movement, they must have access to a visual representation of the anticipated results of the motor act. In addition, Rieser and his colleagues (Rieser et al, 1986) have shown that when people memorize the positions of several objects and then walk blindfolded to a new location, they can quickly and accurately point to the new egocentric positions of the objects. This 'mental updating' seems to be automatic and difficult to inhibit; after memorizing an object's position and moving without vision, it is easier to give the object's new, mentally-updated position than the old, memorized one.…”
Section: Mental Image Transformation and Motor Actionmentioning
confidence: 99%
“…For instance, rotating oneself on a desk chair to take the same visual perspective as a colleague results in a stimulation of the semicircular channels and in the spatial updating of our own body position based on visual and vestibular information (Angelaki & Cullen, 2008). Rieser, Guth, & Hill, (1986) have underlined the importance of vestibular information for spatial localization, by showing that blindfolded participants walking a short distance were well able to keep track of their visuo-spatial perspective. Furthermore, recent work has shown the importance of vestibular information for the experienced first person perspective and for bodily selfconsciousness (Ferre, Bottini, & Haggard, 2011;Ionta et al, 2011;Lopez, Bachofner, Mercier, & Blanke, 2009;Lopez, Lenggenhager, & Blanke, 2010).…”
Section: Introductionmentioning
confidence: 99%